Positive electrode material and preparation method thereof, positive plate, battery and electric equipment
By covering Bi2-xMxO3-δ particles on the core surface of the high-nickel ternary material and doping M metal ions, the problems of structural instability and oxygen release of high-nickel positive electrode materials are solved, and the high capacity and structural stability of the material are achieved.
Patent Information
- Application Number
- CN202411845649.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The structure of high-nickel positive electrode material is unstable under high pressure conditions, resulting in lattice oxygen release, affecting the cycle life and safety of the material.
Bi2-xMxO3-δ particles are coated on the core surface of the high-nickel ternary material. The bond strength of Bi-O metal oxygen bond is reduced by the lonely pair of electrons in Bi's 6s2 electron orbital, stabilizes the lattice oxygen, and adjusts the oxygen vacancy content by doping M metal ions.
Effectively stabilize the lattice oxygen on the surface of high-nickel ternary materials, reduce the reaction between oxygen and electrolyte, inhibit battery heat exothermic and gas production, and improve the structural stability and cycle life of the material.
Smart Images

Figure CN119674002A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries and relates to a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] High-nickel positive electrode materials have the characteristics of high capacity and low cost, and can significantly improve the energy density of batteries. However, high nickel content usually leads to unstable layered structure of the material. Under high pressure conditions, the material usually changes from a layered structure to a spinel or rock salt structure, and the phase change is accompanied by heat release and the release of oxygen atoms in the lattice in the form of oxygen. The escape of oxygen will cause many problems. For example, on the one hand, it will cause changes in the crystal structure of the material, affecting the stability and cycle life of the material. On the other hand, the released oxygen may react with the electrolyte, generating heat, resulting in reduced thermal stability of the material and increasing the risk of thermal runaway. On the other hand, the released oxygen may cause the internal pressure of the battery to increase, which in turn causes safety problems and causes the battery to swell or explode.
[0003] Existing technologies usually alleviate the above problems by increasing the bonding strength between metal and oxygen through surface coating, heteroatom doping, etc. However, existing surface coating methods can only mitigate the side effects caused by lattice oxygen, while doping can easily affect the capacity advantage of high-nickel positive electrode materials themselves.
[0004] Therefore, how to improve the structural stability of high-nickel positive electrode materials is a technical problem that needs to be urgently solved in this field. Summary of the invention
[0005] The present invention provides a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electric device. The positive electrode material of the present invention is obtained by coating Bi with abundant oxygen vacancies on the surface of a high-nickel ternary material core. 2-x M x O 3-δ Particles can stabilize the lattice oxygen on the surface of the core of the high-nickel ternary material, making the positive electrode material have both high capacity and structural stability.
[0006] The first aspect of the present invention provides a positive electrode material, comprising a ternary material core and Bi coated on the surface of the ternary material core. 2-x M x O 3-δ Particles, wherein 0.01≤δ≤1.5, 0≤x≤1, M is selected from Sr 2+ , Ba 2+ , Ca 2+ , Er 3+ , Ln 3+ 、Sm 3+ One or more of;
[0007] The chemical formula of the core of the ternary material is Li(Ni a Co b Mn 1-a-b )O2, where 0.8≤a<1, 0<b≤0.2.
[0008] The positive electrode material as described above, wherein the Bi 2-x M x O 3-δ The ionic conductivity of the particles is 0.01~0.1 S / m;
[0009] And / or, the ionic conductivity of the positive electrode material is 0.32~0.47 S / m.
[0010] The positive electrode material as described above, wherein Bi 2-x M x O 3-δ The mass content of the particles is 1%~15%.
[0011] The positive electrode material as described above, wherein the particle size of the core of the ternary material is 1 μm to 6 μm; and / or the Bi 2-x M x O 3-δ The particle size is 50 nm~500 nm.
[0012] The positive electrode material as described above, wherein the core of the ternary material is a single crystal particle.
[0013] A second aspect of the present invention provides a method for preparing the positive electrode material as described above, the preparation method comprising the following steps:
[0014] Mix Bi(NO3)3·5H2O, M source, precipitant and ternary material core under solid phase conditions for 30min~3h to obtain the positive electrode material;
[0015] The molar ratio of the ternary material core, the Bi(NO3)3·5H2O, the M source and the precipitant is 1:(0.005-0.2):(0-0.1):(0.015-2);
[0016] The precipitating agent is selected from sodium hydroxide and / or potassium hydroxide.
[0017] The preparation method as described above, wherein the mixing reaction is carried out at 20-30°C.
[0018] In the preparation method as described above, the Bi(NO3)3·5H2O and the M source include a dispersion treatment process before use, and the dispersion treatment includes: mixing the Bi(NO3)3·5H2O and the M source with a dispersant, and then grinding the mixture.
[0019] The preparation method as described above, wherein the dispersant comprises one or more of polyethylene glycol, polyvinyl alcohol, and citric acid;
[0020] And / or, the mass ratio of Bi(NO3)3·5H2O to the dispersant is 1:(0.05-0.8).
[0021] The preparation method as described above, wherein after the mixing reaction is completed, it also includes a process of heat treating the reaction product, and the temperature of the heat treatment is 100~300°C.
[0022] The third aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material provided by the first aspect of the present invention or the positive electrode material prepared by the preparation method provided by the second aspect of the present invention.
[0023] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet provided by the third aspect of the present invention.
[0024] A fifth aspect of the present invention provides an electrical device, comprising the battery provided by the fourth aspect of the present invention.
[0025] The implementation of the present invention has at least the following advantages:
[0026] 1) The present invention coats the surface of the high nickel ternary material with non-stoichiometric Bi 2-x M x O 3-δ The particles make the coated particles have certain oxygen vacancies. At the same time, the 6s 2 The presence of lone pairs of electrons in the electron orbit reduces the bond strength of the Bi-O metal oxygen bond. Therefore, the oxygen vacancy has good stability and is not easy to participate in bonding with metal Bi. It has good oxygen adsorption and storage functions in the electrochemical cycle. It is coated on the surface of high-nickel ternary materials to stabilize the surface lattice oxygen, inhibit the overflow of lattice oxygen from the surface, help reduce the formation of surface rock salt phase, maintain the structural stability of the material, and reduce the contact reaction between lattice oxygen and electrolyte, inhibiting the occurrence of battery heat release and gas production.
[0027] 2) The present invention adopts the method of 3-δ Doping with optional Sr 2+ , Ba 2+ , Ca 2+ , Er 3+ , Ln 3+ 、Sm 3+One or more M metal ions in the Bi2O4O4O4O4O4O4O4O4O5 can cause the bulk lattice to distort, change the space environment around the oxygen atoms and the chemical bond length and bond angle, reduce the occupancy stability of oxygen atoms, and increase the concentration of oxygen vacancies. 3-δ The oxygen vacancy content in the nickel matrix can be adjusted to meet the stability requirements of ternary materials with different nickel contents. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0029] Figure 1 This is a SEM morphology image of the positive electrode material of Example 1;
[0030] Figure 2 This is a SEM morphology image of the positive electrode material of Example 2;
[0031] Figure 3 This is a SEM morphology image of the positive electrode material of Example 3;
[0032] Figure 4 This is the SEM morphology of the positive electrode material of Comparative Example 1;
[0033] Figure 5 This is the SEM morphology of the positive electrode material of Comparative Example 2;
[0034] Figure 6 Bi2O on the surface of the positive electrode material of Example 1 2.77 O1s XPS spectrum and peak fitting curve;
[0035] Figure 7 This is the O1s XPS spectrum and peak fitting curve of Bi2O3 on the surface of the positive electrode material of Comparative Example 3. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] As the nickel content increases, the capacity of the ternary material will also increase, but the high nickel content usually causes the material to undergo a phase change, which is accompanied by heat release and the release of lattice oxygen during the phase change. After the lattice oxygen is released, the material will produce oxygen vacancy defects. The oxygen vacancies in the bulk phase will gather to specific crystal planes during the charge and discharge process, accelerating the migration of transition metal ions, leading to crystal plane dislocation and rearrangement, and the generation of microcracks, which will affect the structural stability of the material; at the same time, oxygen vacancies will also accelerate the occurrence of irreversible phase changes, resulting in increased heat release and gas production. And due to kinetic reasons, oxygen vacancy defects on the surface will cause more intense heat release and gas production, and ultimately lead to interface instability. Therefore, how to stabilize the lattice oxygen in high-nickel ternary materials will be of great significance to improving the cyclic stability of the material.
[0038] Based on this, the first aspect of the present invention provides a positive electrode material, comprising a ternary material core and Bi coated on the surface of the ternary material core. 2-x M x O 3-δ Particles, wherein 0.01≤δ≤1.5, 0≤x≤1, M is selected from Sr 2+ , Ba 2+ , Ca 2+ , Er 3+ , Ln 3 + 、Sm 3+ One or more of the following; the chemical formula of the ternary material core is Li(Ni a Co b Mn 1-a-b )O2, where 0.8≤a<1, 0<b≤0.2.
[0039] Compared with the traditional method of coating the inert protective layer on the surface of high nickel ternary materials and bulk doping, the present invention coats Bi on the surface of high nickel ternary materials. 2-x M x O 3-δ Particles, among which Bi 2-x M x O 3-δ It is a non-stoichiometric compound. Non-stoichiometric means that the sum of the positive valences of the cations in the compound is not equal to the sum of the negative valences of the anions. Since the value of δ is 0.01~1.5, the composition of the compound does not meet the stoichiometric ratio, resulting in a certain amount of oxygen vacancies. At the same time, the 6s 2The presence of lone pairs of electrons in the electron orbit reduces the bond strength of the Bi-O metal oxygen bond. Therefore, the oxygen vacancy has good stability and is not easy to participate in bonding with metal Bi. It has good oxygen adsorption and storage functions in the electrochemical cycle. It is coated on the surface of high-nickel ternary materials to stabilize the surface lattice oxygen, inhibit the overflow of lattice oxygen from the surface, help reduce the formation of surface rock salt phase, maintain the structural stability of the material, and reduce the contact reaction between lattice oxygen and electrolyte, inhibiting the occurrence of battery heat release and gas production.
[0040] By using Bi2O 3-δ Doping with optional Sr 2+ , Ba 2+ , Ca 2+ , Er 3+ , Ln 3+ 、Sm 3+ One or more M metal ions in the Bi2O4O4O4O4O4O4O5 can cause the bulk lattice to distort, change the space environment around the oxygen atoms, the chemical bond length and bond angle, reduce the occupancy stability of the oxygen atoms, and increase the concentration of oxygen vacancies. 3-δ The oxygen vacancy content in the nickel matrix can be adjusted to meet the stability requirements of ternary materials with different nickel contents.
[0041] Too little oxygen vacancy content makes it difficult to improve the structural stability of high nickel ternary materials. 2- x M x O 3-δ It is amorphous and difficult to obtain a stable crystal structure. The disorder of the amorphous structure will affect the migration ability of the lattice oxygen and weaken the Bi 2-x M x O 3-δ The ability to absorb and store oxygen is still difficult to stabilize the lattice oxygen on the surface of high-nickel ternary materials. The present invention controls the value of δ to be 0.01~1.5, which can make Bi 2-x M x O 3-δ It has a crystalline structure and a suitable oxygen vacancy content, and has a good ability to adsorb and store lattice oxygen.
[0042] The present invention is to 2-x M x O 3-δ The coating form of the particles on the surface of the ternary material core is not specifically limited, and can be either continuous coating or island coating. Island coating is more preferred, because the island coating not only stabilizes the lattice oxygen on the surface of the high-nickel ternary material, but also provides sufficient area for the deintercalation of lithium ions, which is beneficial to the performance of the material capacity.
[0043] In addition, the present invention will Bi 2-x Mx O 3-δ The particles are coated on the surface of the high-nickel ternary material, and no impurity atoms are doped into the bulk phase, which has no effect on the crystal structure of the high-nickel ternary material. Therefore, the capacity of the high-nickel ternary material will not be lost, so that the material can still maintain a relatively high capacity.
[0044] In a specific embodiment, Bi 2-x M x O 3-δ The ionic conductivity of the particles is 0.01~0.1 S / m. Within the above ionic conductivity range, the oxygen released from the core of the ternary material can be effectively adsorbed and stored. Specifically, the type of M and the values of x and δ can be controlled to regulate the ionic conductivity.
[0045] For example, Bi 2-x M x O 3-δ The ionic conductivity of the particles may be 0.01 S / m, 0.02 S / m, 0.03 S / m, 0.04 S / m, 0.05 S / m, 0.06 S / m, 0.07 S / m, 0.08 S / m, 0.09 S / m, 0.1 S / m or a range consisting of any two of the above values.
[0046] In a specific embodiment, the ionic conductivity of the positive electrode material is 0.32-0.47 S / m. By coating Bi 2-x M x O 3-δ The particles can also make the ionic conductivity of the positive electrode material meet the above range, which is beneficial to the movement of lithium ions in the positive electrode material and improves the charge and discharge rate of the battery. Exemplarily, the ionic conductivity of the positive electrode material can be 0.32, 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, 0.45, 0.47 or a range consisting of any two of the above values.
[0047] It is understandable that Bi 2-x M x O 3-δ When the mass content of the particles is high, although it can better stabilize the lattice oxygen on the surface of the high-nickel ternary material, it will also lead to a decrease in the overall capacity of the positive electrode material. 2-x M x O 3-δ The mass content of the particles is controlled within the range of 1% to 15%, which enables the positive electrode material to have both good structural stability and high capacity. 2-x M x O 3-δThe mass content of the particles can be 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15% or a range consisting of any two of the above values.
[0048] In a preferred embodiment, the core of the ternary material is a single crystal particle. Compared with polycrystalline particles, single crystal particles have a continuous crystal structure and do not contain grain boundaries in polycrystalline particles. Grain boundaries are usually active areas of electrochemical reactions and are prone to cause side reactions. Therefore, the use of single crystal particles can further improve the cycle stability of the positive electrode material.
[0049] In a preferred embodiment, the particle size of the core of the ternary material is 1 μm~6 μm. Although a smaller particle size is beneficial to shorten the diffusion path of lithium ions, improve ion conductivity and battery rate performance, it also means that the material has a larger specific surface area, which will lead to an increase in side reactions between the positive electrode material and the electrolyte, and increase the risk of electrolyte decomposition and interface instability. Controlling the particle size of the core of the ternary material within the above range is conducive to making the material have both higher ion conductivity and better interface stability. Exemplarily, the particle size of the core of the ternary material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm or a range consisting of any two of the above values.
[0050] Nano-Bi 2-x M x O 3-δ The particles have a high specific surface area and good adhesion on the surface of the core, which can provide a good coating effect. 2-x M x O 3-δ The particle size is 50 nm~500 nm. In the above particle size range, Bi 2-x M x O 3-δ The particles can form a good coating on the surface of the core. 2-x M x O 3-δ The particle size of the particles is 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or a range consisting of any two of the above values.
[0051] A second aspect of the present invention provides a method for preparing the positive electrode material as described above, the method comprising the following steps:
[0052] Bi(NO3)3·5H2O, M source, precipitant, and ternary material core are mixed and reacted under solid phase conditions for 30 min to 3 h to obtain a positive electrode material;
[0053] Among them, the molar ratio of the ternary material core, Bi(NO3)3·5H2O, M source and precipitant is 1:(0.005~0.2):(0~0.1):(0.015~2);
[0054] The precipitating agent is selected from sodium hydroxide and / or potassium hydroxide.
[0055] The M source refers to a compound containing M ions, including but not limited to one or more of nitrates, sulfates, carbonates, oxalates, and chlorides of M ions.
[0056] In the above preparation method, Bi(NO3)3·5H2O is used as the Bi source. This component contains crystal water. When mixed with the M source and sodium hydroxide and / or potassium hydroxide for 30 min to 3 h under solid phase conditions, the local temperature of the reactants can be increased, and precipitation can be achieved at room temperature. By solid phase mixing at room temperature, Bi can be in situ formed on the surface of the core of the ternary material. 2-x M x O 3-δ This method avoids the complicated process of hydrolysis and precipitation in the traditional liquid phase coating process, and can complete Bi at a lower temperature without high temperature heating. 2-x M x O 3-δ The synthesis process is simple and suitable for large-scale production.
[0057] In the above preparation process, Bi(NO3)3·5H2O can be formed by controlling the reaction time of solid phase mixing, the molar ratio of Bi(NO3)3·5H2O and the precipitant, and the type of doped M element. 2-x M x O 3-δ The control principle is as follows: (1) the effect of reaction time: within the reaction time of 30min~3h, reducing the reaction time can enhance the non-uniformity of the reaction, resulting in more oxygen vacancies, while prolonging the reaction time can make the reaction more complete and uniform, reducing oxygen vacancies; (2) the effect of the ratio of reactants to precipitants: the present invention controls the molar amount of the reactant Bi(NO3)3·5H2O to be less than the molar amount of the precipitant, which can make Bi(NO3)3·5H2O 2-x M x O 3-δ The crystallinity of the particles is reduced, which is conducive to the generation of oxygen vacancies; (3) Effect of M element doping: M element doping can change the lattice environment and reaction path, and 3+ The incorporation of heterovalent divalent M elements or trivalent M elements with a large difference in atomic radius from Bi will cause the bulk lattice to be distorted, change the spatial environment around the oxygen atoms and the chemical bond length and bond angle, reduce the occupancy stability of oxygen atoms, and increase the concentration of oxygen vacancies.
[0058] Exemplarily, the mixing reaction time can be 30 min, 1 h, 1.5 h, 2 h, 2.5 h, 3 h or a range consisting of any two of the above values.
[0059] In order to make the above raw materials react better under solid phase conditions, the raw materials can be ground during and before the mixing reaction to increase the contact area between the raw materials. A ball mill or other stirring device can also be used for mixing during the mixing reaction. The present invention does not specifically limit the stirring speed, as long as the mixing effect can be achieved.
[0060] The present invention does not specifically limit the source of the ternary material core, which can be purchased commercially or prepared using conventional preparation methods in the art.
[0061] The above mixing reaction is completed by utilizing the exothermic energy of mixing between the raw materials, so no additional heating is required and the mixing can be performed at room temperature, specifically at 20-30°C.
[0062] In a preferred embodiment, Bi(NO3)3·5H2O and M source include a dispersion treatment process before use, wherein the dispersion treatment includes: mixing Bi(NO3)3·5H2O and M source with a dispersant, and then grinding the mixture.
[0063] By dispersing Bi(NO3)3·5H2O and M source, the agglomeration of small particles can be avoided, which is more conducive to the formation of a coating on the surface of the ternary material core and the occurrence of mixing of the agglomerated particles with the ternary material core.
[0064] In a preferred embodiment, the dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, and citric acid. The above dispersants have good lubrication effects, can reduce friction between particles, and thus prevent the occurrence of agglomeration.
[0065] In a preferred embodiment, the mass ratio of Bi(NO3)3·5H2O to the dispersant is 1:(0.05~0.8). Within the above mass ratio range, both the Bi(NO3)3·5H2O and the M source can be fully dispersed and the cost increase caused by excessive dispersant can be avoided. Exemplarily, the mass ratio of Bi(NO3)3·5H2O to the dispersant can be 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8 or a range consisting of any two of the above mass ratios.
[0066] In a specific embodiment, after the mixing reaction is completed, the reaction product is further subjected to a heat treatment process at a temperature of 100 to 300°C. Heat treatment within the above temperature range can decompose and remove excess dispersant, enhance the bonding strength between the core and the surface Bi of the ternary material, and improve the thermal conductivity of the ternary material. 2-x M x O 3-δ The bonding force between particles. For example, the temperature of the heat treatment can be 100° C., 150° C., 200° C., 250° C., 300° C. or a range consisting of any two of the above values.
[0067] It is worth mentioning that if the required Bi 2-x M x O 3-δ The oxygen vacancy δ value in the Bi-O bond is low. In order to stabilize the Bi-O bond and avoid the increase of oxygen vacancies during the heat treatment, the heat treatment can be carried out in an oxidizing oxygen atmosphere. 2-x M x O 3-δ The oxygen vacancy δ value is relatively high. In order to stabilize the oxygen vacancies and avoid the reduction of oxygen vacancies during heat treatment, heat treatment can be carried out in a reducing hydrogen atmosphere.
[0068] In a specific embodiment, after the mixing reaction is completed, before the reaction product is subjected to heat treatment, the reaction product is further subjected to a washing process to remove the residual precipitant in the product. The reaction product can be washed with deionized water or ultrapure water until the washing liquid is neutral. After washing, the product can be dried to avoid the adverse effects of the residual washing liquid on the product.
[0069] The third aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material provided by the first aspect of the present invention or the positive electrode material prepared by the preparation method provided by the second aspect of the present invention.
[0070] Since the positive electrode sheet of the present invention includes the positive electrode material having both high capacity and structural stability, the positive electrode sheet can also have both high capacity and good structural stability during application.
[0071] The present invention does not particularly limit the positional relationship between the positive electrode current collector and the positive electrode active material layer. The positive electrode active material can be directly disposed on one or both sides of the positive electrode current collector, or other functional layers or primer layers can be included between the positive electrode current collector and the positive electrode active material layer.
[0072] The present invention does not impose any particular limitation on the positive electrode current collector, and any current collector commonly used in the art, such as aluminum foil, can be used, which can be commercially available.
[0073] In addition to the above-mentioned positive electrode materials, the positive electrode active material layer of the present invention also includes components such as a conductive agent and a binder. Among them, the conductive agent and the binder can be selected from materials commonly used in the art. Specifically, the conductive agent can be selected from one or more of conductive carbon black, acetylene black, Ketjen black, and carbon nanofibers, and the binder can be selected from one or more of PVDF, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, and styrene-butadiene rubber.
[0074] The present invention does not specifically limit the preparation method of the positive electrode sheet, and the positive electrode sheet can be prepared by conventional preparation methods in the art. For example, the positive electrode material, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive electrode current collector, and the positive electrode sheet can be obtained after drying, slitting and rolling.
[0075] The fourth aspect of the present invention provides a battery, comprising the positive electrode sheet provided by the third aspect of the present invention. Since the battery comprises the positive electrode sheet having both high capacity and structural stability, the battery has good cycle stability and thermal stability during the charge and discharge process, and can suppress the occurrence of phenomena such as battery gas production and bulging.
[0076] The battery of the present invention comprises, in addition to the positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0077] Among them, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector can be selected from the negative electrode current collectors conventionally used in the art, such as copper foil. The negative electrode active material layer can also refer to the conventional composition in the art, for example, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. Among them, the negative electrode active material can be selected from the negative electrode active materials conventionally used in the art, including but not limited to one or more of natural graphite, artificial graphite, silicon-carbon material, silicon-oxygen material, and hard carbon. The composition of the conductive agent and the binder can refer to the types of conductive agents and binders in the positive electrode sheet, which will not be repeated here.
[0078] The present invention does not specifically limit the preparation method of the negative electrode sheet, and it can adopt a conventional preparation method in the art. For example, the negative electrode active material, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive electrode collector, and the negative electrode sheet can be obtained after drying, slitting and rolling.
[0079] The function of the separator is to separate the positive electrode sheet from the negative electrode sheet and provide a channel for lithium ion migration. The present application does not specifically limit the type of separator, and any separator commonly used in the art, such as a polypropylene separator, a polyethylene separator, etc., can be used.
[0080] The present invention does not specifically limit the type of electrolyte, and the electrolyte may be selected from liquid electrolytes, solid electrolytes or gel electrolytes commonly used in the art.
[0081] The battery of the present invention can be prepared by referring to conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and then a battery cell is obtained through a lamination or winding process, and then the battery of the present invention is obtained through baking, liquid injection, formation, packaging and other processes.
[0082] The fifth aspect of the present invention provides an electric device, comprising the battery provided in the fourth aspect of the present invention. The present invention does not specifically limit the type of electric device, and it can be any electric device including the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, lighting equipment, cameras, etc.
[0083] The positive electrode material provided by the present invention is further described in detail below in conjunction with specific embodiments.
[0084] Example 1
[0085] This embodiment provides a positive electrode material, and the preparation method thereof comprises the following steps:
[0086] 1) Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium hydroxide are mixed in a solid phase at a molar ratio of 1:1.1 to obtain a mixture; the mixture is kept at 300°C for 2 hours and then at 800°C for 15 hours in an oxygen atmosphere, and then cooled, crushed and sieved to obtain granular single crystal LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), particle size 2~4μm;
[0087] 2) Grind NaOH and Bi(NO3)3·5H2O in a molar ratio of 0.005:0.015 respectively to grind the flaky solid into a powder solid;
[0088] 3) The ground Bi(NO3)3·5H2O and dispersant polyethylene glycol were uniformly mixed in a mass ratio of 1:0.05 and then ground to obtain a mixture; the ground NaOH, the mixture and the prepared single crystal NCM811 were mixed, and the mixture was stirred at room temperature for 3 h in a stirring device to obtain a product;
[0089] Among them, the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.005: 0.015;
[0090] 4) washing the product with deionized water until the washing liquid is neutral, and drying at 80°C;
[0091] 5) The dried product was heat treated at 100°C for 1 h in an air atmosphere, and then cooled to obtain the positive electrode material.
[0092] Example 2
[0093] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of Example 1, except that in step 3), the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.005: 0.05, the stirring time is 30 min, and the heat treatment temperature in step 5) is 300°C.
[0094] Example 3
[0095] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that in step 1), Ni 0.8 Co 0.1 Mn 0.1 (OH)2 replaced by Ni 0.92 Co 0.04 Mn 0.04 (OH)2, to prepare granular single crystal Li(Ni 0.92 Co 0.04 Mn 0.04 )O2 (NCM9244), in step 3), the mass ratio of Bi(NO3)3·5H2O and dispersant polyethylene glycol was replaced to 1:0.8.
[0096] Example 4
[0097] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that step 3) is replaced by:
[0098] The ground Bi(NO3)3·5H2O, the ground SrNO3·4H2O and the dispersant polyethylene glycol are uniformly mixed and then ground to obtain a mixture, and the mass ratio of Bi(NO3)3·5H2O to the dispersant polyethylene glycol is 1:0.05 during the mixing process;
[0099] The ground NaOH, the mixed material and the prepared single crystal NCM811 were mixed, and then stirred at room temperature for 3 h in a stirring device to obtain a product;
[0100] Among them, the molar ratio of NCM811, Bi(NO3)3·5H2O, SrNO3·4H2O and NaOH is 1: 0.0045:0.0005: 0.015.
[0101] Example 5
[0102] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of embodiment 4, except that SrNO3·4H2O in step 3) is replaced by Er2(SO4)3·8H2O.
[0103] Example 6
[0104] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of Example 1, except that in step 3), the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.01: 0.005, and the stirring time at room temperature in the stirring device is 20 min.
[0105] Example 7
[0106] This embodiment provides a positive electrode material, and its preparation method is basically the same as that of Example 1, except that in step 3), the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.1: 0.2, and the stirring time at room temperature in the stirring device is 1 h.
[0107] Example 8
[0108] This embodiment provides a positive electrode material, and its preparation method is different from that of embodiment 1 in that the room temperature stirring time in step 3) is 10 minutes, and step 5) is replaced by: heat treating the dried product at 300° C. for 1 hour in an oxygen atmosphere.
[0109] Example 9
[0110] This embodiment provides a positive electrode material, and its preparation method is different from that of Example 1 in that the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH in step 3) is 1: 0.005: 2, the stirring time at room temperature is 2 h, and step 5) is replaced by: in a hydrogen atmosphere, the dried material is kept at 300°C for 1 h.
[0111] Comparative Example 1
[0112] This comparative example provides a positive electrode material, and its preparation method is different from that of Example 1 in that steps 2) to 5) in Example 1 are omitted, and the positive electrode material obtained is LiNi 0.8 Co 0.1 Mn 0.1 (NCM811).
[0113] Comparative Example 2
[0114] This comparative example provides a positive electrode material, and its preparation method is different from that of Example 3 in that steps 2) to 5) in Example 3 are omitted, and the positive electrode material obtained is Li(Ni 0.92 Co 0.04 Mn 0.04 )O2 (NCM9244).
[0115] Comparative Example 3
[0116] This comparative example provides a positive electrode material, and its preparation method is different from that of Example 1 in that, in step 3), the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.001: 0.001, and the stirring time at room temperature is 30 min.
[0117] Comparative Example 4
[0118] This comparative example provides a positive electrode material, and its preparation method is different from that of Example 1 in that, in step 3), the molar ratio of NCM811, Bi(NO3)3·5H2O and NaOH is 1: 0.5: 1.5, and the stirring time at room temperature is 45 min.
[0119] Test Case
[0120] 1. The following parameters were tested on the positive electrode materials of the above embodiments and comparative examples:
[0121] 1. XRD phase ratio analysis
[0122] Test method: First grind the sample into fine powder, measure it with XRD instrument, set the scanning range to 5°~90°, the scanning speed to 1°~2° to collect data, and obtain XRD graph. According to the XRD graph analysis, the Bi content in the positive electrode material is 2-x M x O 3-δ The values of phase content and NCM phase content.
[0123] 2. NCM core and Bi 2-x M x O 3-δ Particle size
[0124] Test method: SEM was used to observe the morphology of the positive electrode material and obtain the NCM core and Bi 2-x M x O 3-δ The particle size range value.
[0125] Figure 1~Figure 5 The SEM morphology images of the positive electrode materials of Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1. Figures 1 to 5It can be seen that the surface of the NCM particles of Examples 1 to 3 is covered with dot-shaped nano-Bi 2-x M x O 3-δ Particles, wherein the surface of the NCM particles of Example 2 is coated with nano Bi 2-x M x O 3-δ The particles are relatively the most, while the particles in Comparative Examples 1 and 2 are smooth and uncoated.
[0126] 3.Bi 2-x M x O 3-δ The δ value
[0127] Test method: Use X-ray photoelectron spectrometer (XPS) to ensure high vacuum in the sample chamber and scan the narrow spectrum of O. Use Gauss-Lorentz function fitting to distinguish O in different chemical environments and determine the sub-peak area. The δ value is obtained by combining the peak area ratio, valence state and chemical formula.
[0128] Figure 6 Bi2O on the surface of the positive electrode material of Example 1 2.77 O1s XPS spectrum and peak fitting curve, from Figure 6 It can be seen that there are three main peaks in the XPS spectrum after peak fitting, which are located at about 530 eV (peak A), about 531.2 eV (peak C), and about 532.7 eV (peak B), corresponding to Bi2O 2.77 The lattice oxygen, oxygen vacancies and H2O adsorbed on the surface of the material. The peak area of peak A is 5980, and the peak area of peak C is 488. According to 488 / (5980+488)×3, the non-stoichiometric ratio of oxygen element can be calculated to be 0.23, and the chemical formula is Bi2O 2.77 .
[0129] Figure 7 The O1s XPS spectrum and peak fitting curve of Bi2O3 on the surface of the positive electrode material of Comparative Example 3 are shown in Table 1. Figure 7 It can be seen that after peak fitting, its XPS spectrum has two main peaks, located at about 530 eV (peak A) and about 532.7 eV (peak B), and there is no peak C representing oxygen vacancies.
[0130] 4.Bi 2-x M x O 3-δ and the ionic conductivity of the cathode material
[0131] Test method: The same synthesis process as in the example was used, except that the ternary material core was not introduced during the preparation process, and only Bi 2-x M x O3-δ Single-phase material. Place the material in a high-temperature furnace and connect the electrodes and measuring circuits.
[0132] The prepared Bi 2-x M x O 3-δ The conductivity of the single-phase material and the positive electrode material is measured to obtain the Bi 2-x M x O 3-δ and the ionic conductivity of the cathode material.
[0133] The test results of the above parameters are listed in Table 1.
[0134] 2. The positive electrode materials of the above embodiments and comparative examples are respectively prepared into button cells and soft-pack cells, and the preparation methods are as follows:
[0135] A. Button battery:
[0136] The positive electrode material, the conductive agent SP and the binder PVDF were mixed in a mass ratio of 95:2.5:2.5 and added to the solvent NMP to make a slurry, which was applied on an aluminum foil, dried and pressed to obtain a positive electrode sheet;
[0137] In a glove box filled with argon, the button cell was assembled in the order of negative electrode shell, gasket, lithium sheet, PP diaphragm, positive electrode sheet, gasket, spring, and positive electrode shell, and then the electrolyte was dripped into the cell. The button cell was charged to 100% SOC using 0.2C;
[0138] The electrolyte includes a solvent and a lithium salt, the solvent is a mixture of EC, DMC and DEC in a volume ratio of 1:1:1, the lithium salt is LiPF6, and the concentration of the lithium salt in the electrolyte is 1.0 mol / L.
[0139] B. Soft pack battery:
[0140] The positive electrode material, the conductive agent SP and the binder PVDF were mixed in a mass ratio of 95:2.5:2.5 and added to the solvent NMP to prepare a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil, dried, and pressed to obtain a positive electrode sheet.
[0141] The negative electrode material artificial graphite, the conductive agent SP and the binder CMC are mixed in a mass ratio of 95:2.5:2.5, dispersed in deionized water to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, dried, and pressed to obtain a negative electrode sheet;
[0142] The positive electrode sheet, PP separator and negative electrode sheet are stacked in sequence and wound to obtain a battery cell, and then the battery cell is placed in an aluminum-plastic film packaging bag, and the electrolyte is injected to seal the bag, and the soft-pack battery is obtained after the electrolyte is formed;
[0143] The electrolyte includes a lithium salt and a solvent, wherein the solvent is a mixture of EC, DMC, DEC, FEC and VC in a volume ratio of 30:30:20:18:2, and the lithium salt is LiPF6, and its concentration is 1.0M LiPF6.
[0144] The prepared battery was tested for the following properties:
[0145] 1. Thermal decomposition performance
[0146] Test method: Remove the positive electrode sheet of the button battery charged to 100% SOC in the glove box, transfer it to the DSC sample dish, seal it and place it in the DSC instrument. Set the heating rate to 1℃ / min, test within 30-400℃, and record the curve of heat flow changing with temperature. Observe the DSC curve, and the temperature corresponding to the peak value can reflect the temperature at which the material undergoes thermal reaction. Compare the DSC curves of different materials or materials in different states, and record the decomposition starting temperature and decomposition peak temperature of the battery. If the curve moves toward high temperature or the heat release decreases, it means that the thermal stability of the material has improved.
[0147] 2. Volume growth rate
[0148] Test method: Pour electrolyte into a transparent container with scale, record the initial volume, then place the soft-pack battery in it to measure the volume, and calculate the initial volume V1 of the battery by the difference between the two; charge the soft-pack battery to 100% SOC and store it at 70°C for 7 days. After storage, place the soft-pack battery in a transparent container with scale again and measure the volume at this time, which is the volume V2 of the battery stored at 70°C for 7 days. Calculate the battery's 70°C inflation volume growth rate by (V2-V1) / V1×100%.
[0149] 3. 1C battery capacity
[0150] Test method: Connect the button cell to a professional battery test system, set the discharge current to 1C, start the discharge operation, and record the voltage, current and time data during the discharge process. The discharge continues until the cut-off voltage reaches 2.8V. By integrating the discharge current and time, the actual capacity of the battery at a 1C discharge rate can be obtained.
[0151] 4. Cycle capacity retention rate
[0152] Test method: Connect the soft-pack battery to a professional battery test system and test it in a 45°C constant temperature box. Set the charge and discharge current to 1C, the voltage range to 2.5V ~ 4.25V, start the cycle test, and record the voltage, current and time data during the process. By integrating the current and time, the actual capacity of the battery at a 1C discharge rate is obtained. After 100 cycles, the cycle capacity retention rate is calculated based on the initial capacity.
[0153] The test results of the above performance are listed in Table 2.
[0154] Table 1
[0155]
[0156] Table 2
[0157]
[0158] Combining Table 1 and Table 2, we can draw the following conclusions:
[0159] 1) By comparing Examples 1-2 with Comparative Example 1 and Example 3 with Comparative Example 2, it can be seen that the Bi2O with oxygen defects coated on the surface of NCM811 and NCM9244 3-δ The particles can increase the thermal decomposition starting temperature and peak temperature of the positive electrode material and the cycle capacity retention rate of the battery, and the volume growth rate during the charge and discharge process is also significantly reduced. 3-δ The particles lead to a slight decrease, but it is still within the normal range, with no obvious difference. This shows that the positive electrode material of the present invention is coated with Bi2O on the surface of the high nickel ternary material core. 3-δ Particles can significantly improve the thermal stability and cycle stability of materials.
[0160] 2) By comparing Examples 4 to 5 with Comparative Example 1, it can be seen that the surface of NCM811 and NCM9244 is coated with Bi with oxygen defects. 2-x M x O 3-δ The particles can further increase the thermal decomposition starting temperature and peak temperature of the positive electrode material and the capacity retention rate of the battery, and the volume growth rate during the charge and discharge process is also reduced. 3-δ The particles lead to a slight decrease, but it is still within the normal range, with no obvious difference. This shows that the positive electrode material of the present invention is coated with Bi on the surface of the high nickel ternary material core. 2-x M x O 3-δ Particles can significantly improve the thermal stability and cycle stability of materials.
[0161] 3) By comparing Examples 6 to 7 with Comparative Example 1, it can be seen that when Bi 2-x M x O 3-δ When the phase content is 0.75%, the thermal decomposition starting temperature and peak temperature of the positive electrode material do not increase significantly, the gas volume growth rate does not decrease significantly, and the cycle capacity retention rate increases slightly, which has limited effect on the thermal stability of the material and the improvement of battery gas performance. 2-x M x O 3-δ When the phase content is 18%, the thermal decomposition starting temperature, peak temperature and cycle capacity retention rate of the positive electrode material are all improved, indicating that the thermal stability and cycle performance of the positive electrode material are improved, but the battery capacity of the material is significantly reduced. 2-x M x O 3-δ Too high or too low a coating amount of the phase is not conducive to improving the comprehensive performance of the positive electrode material.
[0162] 4) By comparing Examples 1, 8, 9 and Comparative Examples 1, 3, 4, it can be seen that directly using bismuth oxide without oxygen vacancies to coat the high nickel ternary material (Comparative Example 3) has no effect on improving the thermal stability of the material, nor can it inhibit the flatulence of the battery. The cycle capacity retention rate of the battery is also average, and even leads to a decrease in the capacity of the material. When the introduced Bi2O 3-δ When the oxygen vacancy content δ is greater than 1.5 (Comparative Example 4), due to the large oxygen loss, Bi2O 3-δ The orderliness of the crystal structure is significantly reduced, and lattice oxygen cannot be effectively stored and adsorbed, so the material has no improvement in thermal stability, cycle stability and flatulence; when the oxygen vacancy δ is 0.1 and 1.5 (Examples 8 and 9), the thermal stability, cycle performance and flatulence performance of the material are improved, and the material capacity is not significantly reduced. Among them, when the oxygen vacancy δ is 0.23 (Example 1), the thermal stability, cycle performance and flatulence performance of the material are improved more significantly, indicating that the δ value should not be too high or too low.
[0163] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention, which follow the general principles of the present invention and include common knowledge or customary technical means in the art not disclosed by the present invention, are not limited to the precise structure described above and shown in the drawings, and may be modified and changed in various ways without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a ternary material core and a Bi 2-x M x O 3-δ Particles, wherein 0.01≤δ≤1.5, 0≤x≤1, M is selected from Sr 2+ , Ba 2+ , Ca 2+ , Er 3+ , Ln 3+ 、Sm 3 + One or more of; The chemical formula of the core of the ternary material is Li(Ni a Co b Mn 1-a-b )O2, where 0.8≤a<1, 0<b≤0.
2.
2. The positive electrode material according to claim 1, characterized in that The Bi 2-x M x O 3-δ The ionic conductivity of the particles is 0.01~0.1 S / m; And / or, the ionic conductivity of the positive electrode material is 0.32~0.47 S / m.
3. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material contains Bi 2-x M x O 3-δ The mass content of the particles is 1%~15%.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The particle size of the core of the ternary material is 1 μm to 6 μm; and / or, the Bi 2-x M x O 3-δ The particle size is 50 nm~500 nm.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that The core of the ternary material is a single crystal particle.
6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Mix Bi(NO3)3·5H2O, M source, precipitant and ternary material core under solid phase conditions for 30min~3h to obtain the positive electrode material; The molar ratio of the ternary material core, the Bi(NO3)3·5H2O, the M source and the precipitant is 1:(0.005-0.2):(0-0.1):(0.015-2); The precipitating agent is selected from sodium hydroxide and / or potassium hydroxide.
7. The preparation method according to claim 6, characterized in that: The mixing reaction is carried out at 20-30°C.
8. The preparation method according to claim 6 or 7, characterized in that: The Bi(NO3)3.5H2O and the M source are subjected to a dispersion treatment process before use, and the dispersion treatment comprises: mixing the Bi(NO3)3.5H2O and the M source with a dispersant, and then grinding the mixture.
9. The preparation method according to claim 8, characterized in that: The dispersant includes one or more of polyethylene glycol, polyvinyl alcohol, and citric acid; And / or, the mass ratio of Bi(NO3)3·5H2O to the dispersant is 1:(0.05-0.8).
10. The preparation method according to claim 8 or 9, characterized in that: After the mixing reaction is completed, the process further includes heat treating the reaction product, wherein the temperature of the heat treatment is 100-300°C.
11. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer, characterized in that: The positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the preparation method according to any one of claims 6 to 10.
12. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 11.
13. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 12.
Citation Information
Cited By
Wide-temperature-range lithium iron phosphate power battery and preparation method thereof
CN121035377A
A wide-temperature-range lithium iron phosphate power battery and a preparation method thereof
CN121035377B